(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A new morpho-syntactic interpretation of the Iberian inscription of Cruzy is proposed. IubebaĚete, with the suffix –te, it would be the subject. The indirect complement would correspond to neitin iunstir kuleĞare, with an –e dative morpho, neitin and kuleĞar are in apposition to iunstir. Finally, in arkiteibase a direct object arki (ayki), and a verbal inflection teibase could be distinguished, both of them of unknown meaning, but the last one with a –se morpho, maybe a pronominal one.